Learning orientation and response of micro and small food agro-processing enterprises to the customers' needs in Tanzania - Eliakira Nnko; Ismail J. Ismail; Elia John (Cogent Business & Management, 2024)
Response to customers' needs is considered a key to success of micro and small food agro-processing enterprises. However, these firms tend lose customers as a result of fast changing customers' tastes and preferences in the market. Arguments are directed on the learning culture of micro and small food processing enterprises to appropriately capture and provide for the requirements of customers. This paper assessed the learning orientation of micro and small food agro-processing enterprises by specifically determine the extent to which learning orientation influence the response of micro and small food agro-processing firms to the customers' needs. The study employed quantitative method approach and a cross sectional survey design. A stratified sampling technique was used in the study, whereby data were collected using structured questionnaire from 302 owner-managers in Arusha, Morogoro and Dar es Salaam regions in Tanzania. The collected data were analysed using descriptive statistics and multiple linear regression. The findings revealed statistically significant relationship between learning orientation and response of micro and small food agro-processing enterprises to customers' needs. More specifically, commitment to learning was found to be positive significant related to response to customers' needs. Again, open-mindedness was found to be positive and significant related to response to customers' needs. Furthermore, the relationship between shared vision and response to customers' needs was found to be positive and significant. The results provide an implication that, enterprises with strong learning orientation are in better position to respond to customers' needs than enterprises with low learning orientation. This shows that, to be able to appropriately respond to the needs of the customers, the entrepreneurs need to put commitment in learning, open-up for new ideas and information and have a shared-vision which provide a clear direction for learning. This study advocates for policy makers and trainers to establish relevant tools to support learning environment for the micro and small enterprises to improve response to the varying needs of customers in the market.
Keywords: 650; Learning orientation; food agro-processing; MSEs; response to customers' needs